Improving Students Engagement Through Active Learning Strategies: Case Study Based Active Review Sessions and Skillathon - Patil, Sachin S.; Dharwadkar, Nagaraj V. (Journal of Engineering Education Transformations, 2020)
Today's z-generation student is more captivated with hand-held devices involving e-participation such as virtual games, Github repository creation, e-netizen and many more. It implicitly points towards participative learning through engagement. There is a need in shift of paradigm wherein the teaching-learning strategy should emphasize for student's participation to increase concrete learning. The proposed experimentations in this work is to share two active learning strategies viz. Case study based Active Review Sessions and Skillathon, which have practiced and experienced during the delivery of B Tech and M Tech courses. These two methodologies have been chosen with certain motivations to improve student's engagement for learning, elevate collaborative learning together with complying Outcome based Education (OBE). Additionaly, they have helped to retain the experienced knowledge with joyful status. These techniques were guided with some definite suitability to address the prior discrepancy of course attainments and improve its outcome. The students were found ardent in participative learning connecting these strategies. The post activity analysis has shown a notable rise in student's performance.